Micro-encapsulation of Si-Fe ultra-high temperature phase change material: Fabrication and basic energy storage properties - Wojciech Polkowski; Paolo Lai Zhong Lo Biundo; Jianmeng Jiao; Maria Wallin; Bartosz Kalicki; Jakub Ciftci; Łukasz Żrodowski; Adelajda Polkowska; Aleksandra Bętkowska; Filip Kateusz; Merete Tangstad (Results in Engineering)
A micro-encapsulation technique has been proposed as an efficient way to protect metallic phase change materials (PCM) against degradation of its properties due to environmental and corrosion effects. So far, this technique has been mostly applied to Al-based metallic PCMs operating at temperatures below 700 °C and giving storing capacities of 180–370 Jg-1. In this work, a micro-encapsulation approach was introduced for the first time to a binary eutectic Si-Fe ultra-high temperature PCM predicted to work at temperatures even higher than 1200 °C and providing few times larger stored energy (at a level of 1000 Jg-1). A multi-step processing was designed and applied to fabricate spherical microcapsules having a structure of SiO2 shell and the Si-Fe eutectic PCM core. Structure and basic thermophysical properties of Si-Fe microcapsules were experimentally validated in scanning electron microscope (SEM), X-ray diffraction (XRD) and differential scanning calorimetry (DSC) studies. It was documented that the newly developed Si-Fe microcapsules exhibit high thermal energy storage density of ∼1 MWh/m3, strongly exceeding capabilities of lead-acid and Li-ion batteries, as well as these of the current state of the art latent heat thermal energy storage systems utilized in concentrated solar power applications.